Alat Permainan Edukatif (APE) Berbasis Bahan Lingkungan dalam Mengatasi Permasalahan Pembelajaran Pendidikan Anak Usia Dini - Solfema, Solfema; Wahid, Syafruddin; Pamungkas, Alim Harun (Universitas Negeri Padang, 2018)
Education is important for the progress of the nation. Education must be done in a person's life, including for early childhood. The problem is that there are still many early childhood education providers that have not met the expected quality standards. One of the reasons is that there are still limited Educative Game Tools (APE) used by education in the implementation of learning. Many educators claim that it is difficult to get an Educational Game Tool (APE). This problem solving can be done through various trainings, training, training, and the creation of environmental-based Educative Game Tools (APE) needs to be carried out. Training methods are carried out in the form of presentations of theories and practical exercises. The results of the training show that with training activities it was found that the insights and skills of PAUD educators in the procurement and manufacture of Educational Game Tools (APE) based on environmental materials.Keywords: Educational Game Tools (APE), Early Childhood Education (PAUD)